Physicians’ Approach to Obtaining Organ Prior to Legal Autopsy for Transplantation a Study on Inquiries - Elmas, İmdat and Tüzün, Birgül and Akkay, Erdem (The Bulletin of Legal Medicine, 1998)
In this study on inquiries carried out for the purpose of discussing the approach of specialists on forensic medicine regarding the obtainment of pre- autopsy transplantation aimed organ in legal death cases and the deficiencies in legal regulations related with this subject 77 forensic medicine specialists were inquired. Furthermore, a total of 108 specialists and practitioners in various branches who were employed in foundation hospital and super- emergent unit were interviewed with the intention of making a comparison. 84.4 of forensic medicine specialists and other physicians who were inquired reported that obtaining organs prior to autopsy in legal cases might lead to a risk to lose same findings that might be effective in clarifying death mechanism, 74.0 and 72.0% stated that such a procedure might eliminate the possibility of applying autopsy techniques that would clarify death mechanism, and 72.2 and 68.5% indicated that it might affect negatively both histologic and toxicological methods of examination respectively. While 94% of both groups stated that those organs which would not affect legal autopsy could be taken, 6% rejected absolutely to obtaining organs from legal cases. 84.4 of forensic medicine specialists reported that a forensic medicine specialist should be consulted to for his consent that it was not inconvenient in view of autopsy prior to the stage of deciding to obtain organs from legal cases and 83.1 and 87.0% noted that forensic medicine specialist should be present as an observe while obtaining organs and that he should inscribe his views of significance in view of autopsy in the report to be arranged, respectively. More than 90% of both groups emphasized that in obtaining organs in legal cases, permission granted by the prosecutor should be of significance with the prerequisite of obtaining the view of forensic medicine specialist, it was also concluded that new legal arrangements should be made complying with medical ethical and legal regulations in order for medical interventions aiming at obtaining organs in legal death cases to comply with forensic practice and transplantation aims. Key Words: Legal autopsy, Transplantation.